THE INFLUENCE OF ENTREPRENEURIAL MOTIVATION, ENTREPRENEURIAL SELF-EFFICACY, ENTREPRENEURIAL ORIENTATION TOWARD GREEN ENTREPRENEURIAL INTENTION - Nabil Umar Bayu Wisanggeni; Rizkyna Devi Kurniasih; Adi Pratama; Herni Justiana Astuti (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to analyze the influence of Entrepreneurial Motivation, Entrepreneurial Self-Efficacy (ESE), and Entrepreneurial Orientation toward Green Entrepreneurial Intention with ESE as an intervening variable between entrepreneurial motivation and green entrepreneurial intention. The respondent in this study is a management and accounting student-faculty of economics and business University of Muhammadiyah Purwokerto and obtained 71 respondents. The method in this research uses structural equation modeling with a partial least square approach. The result of the study reveals entrepreneurial motivation affect entrepreneurial self-efficacy, entrepreneurial motivation affects green entrepreneurial intention, entrepreneurial orientation does not affect on green entrepreneurial intention, entrepreneurial self-efficacydoes not affect green entrepreneurial intention, and entrepreneurial self-efficacy does not mediate relationship between entrepreneurial motivation toward green entrepreneurial intention.